SHAPING A SUSTAINABLE FUTURE IN THE ENERGY SECTOR - Paul, Calanter (Economics of Agriculture, 2012)
The growing consumption of energy is felt worldwide, and because of this issue the application of measures are required in this area. These measures are stipulated in the framework of policies and strategies in the energy field, whose objectives can be more easily achieved if the principles of sustainable development are taken into account. Confusion is created between these principles and the dimensions of sustainable development; this paper wants to emphasize the difference between the two notions, with examples edifying in this respect. Once the policies and strategies are formulated, things can move in any direction, and to demonstrate this, we considered it appropriate to present scenarios on energy policies and to try to identify where Romania stands right now, according to the axis that separates the two scenarios: a government commitment and degree of cooperation and integration. Starting from the idea that "the main tool in the fight against climate change (...) is the energy policy" (A. Leca, V. Musatescu, 2010), the paper presents the premises of formulating viable policies and strategies, making some observations on Romanias Energy Strategy 2007-2020.